PENGEMBANGAN WISATA BERBASIS MASYARAKAT DI KAWASAN WISATA LAWE GURAH, TAMAN NASIONAL GUNUNG LEUSER - Rachmawati, Eva; Pasaribu, Angelina (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Community-based tourism development is one of the tourism concepts expected to optimize the benefits felt by the community. However, community readiness is needed in its development efforts because they will be the managers and organizers of these development activities. This study aims at the Lawe Gurah community’s preparation to develop community-based tourism activities in their area and realize sustainable community-based tourism. This research was conducted qualitatively by conducting interviews with the community and various stakeholders involved in the development effort. The analytical framework used to identify the condition of community readiness is the stages developed by the Asia-Pacific Economy-Cooperation (APEC). The study results indicate that the Lawe Gurah community has good readiness to develop community-based tourism activities. Based on nine crucial stages, the community has reached stage 6, which means: that the community is ready to develop tourism in their area, the community has basic skills for tourism development, there is leadership and organizational structure for tourism management, there are efforts to advance tourism management organizations, partnership development, adopting an integrated approach. Three more states that have not been achieved are the availability of product plans and designs, preparation of marketing strategies, and implementation and monitoring of the area. Therefore, the community still needs to prepare several things to be more sustainable tourism development. These things are related to tourism development with an integrated approach, the preparation of various tourism products, studies related to tourism demand, and the monitoring and evaluation mechanism of these tourism activities.